Material modification method
By melting and mixing multiple materials and selectively removing one of them, the problem of difficulty in generating diversified pore structures in the prior art is solved, and a highly customized design of the material is achieved, and the performance and function of the material is improved.
Patent Information
- Application Number
- CN202411791106.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-11
AI Technical Summary
Existing material surface modification techniques are difficult to generate materials with diverse pore structures, limiting the versatility of the material in applications such as catalysis, adsorption and filtration.
The highly customized microstructure design of the product material is achieved by melting and mixing various materials into an alloy material and selectively removing one of them.
This method can accurately control the depth and position of alloying in three-dimensional space, design a diverse pore structure, improve the performance and function of the material, and is suitable for a variety of high-end application scenarios.
Smart Images

Figure CN119794372A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material surface modification, and in particular to a material modification method. Background Art
[0002] In modern industrial applications, material surface modification and alloy structure design are key areas for improving material performance. In particular, pore structure plays a vital role in material performance in applications such as catalysis, adsorption, and filtration. An ideal pore structure can not only increase the effective surface area of the material, but also optimize the fluid transmission path, thereby improving reaction efficiency and selectivity.
[0003] However, current material surface modification technologies can usually only produce materials without pores or with a single pore structure when generating alloy structures. For example, traditional electroplating, chemical plating or thermal spraying often generate dense and non-porous alloy layers; although the sintering metal powder process can form a number of micropores, due to the relatively uniform size of the powder particles, the pores finally formed also tend to be evenly distributed and similar in size, making it difficult to adjust within a large range.
[0004] The uniformity of pore structure greatly limits the versatility of materials in specific applications. For example, in heterogeneous catalysis, different catalytic reactions may require pores of different sizes and shapes to promote the selective adsorption and conversion of substrate molecules; in filtration applications, diversified pore structures can achieve more refined fractionation, while a single pore structure is difficult to meet these requirements. Summary of the invention
[0005] The main purpose of the present invention is to propose a method for material modification, which can design the pore structure of the product material.
[0006] To achieve the above objectives, some embodiments of the present invention provide a material surface modification method, comprising: Melting and mixing a plurality of materials to form an alloy material; wherein the plurality of materials include a first material and a second material; The first material in the alloy material is removed.
[0007] In some embodiments, the plurality of materials includes only the first material and the second material; or, the plurality of materials includes three or more materials.
[0008] In some embodiments, removing the second material from the alloy material includes: Reacting with the first material by a solution or vapor to remove the first material from the alloy material; or The solution or steam reacts with the first material and at least one other material respectively to remove two or more materials in the alloy material.
[0009] In some embodiments, melt mixing a plurality of materials to form an alloy material comprises: Mixing a plurality of materials by laser melting to form an alloy material; and / or, The laser is controlled to scan multiple materials multiple times to form an alloy material.
[0010] In some embodiments, melt mixing a plurality of materials to form an alloy material comprises: The laser focus is controlled to stay in at least one region of multiple materials for a time t, where the range of t is: 1ns≤t≤40s.
[0011] In some embodiments, melt mixing a plurality of materials to form an alloy material comprises: Controlling the laser so that the focus of the laser passes through at least the first area and the second area; and / or, Controlling the laser so that the focus of the laser passes through at least the third area and the fourth area; The first direction is the direction from the first material to the second material. Along the first direction, the first region and the second region are spaced apart. Along the second direction, the third region and the fourth region are spaced apart. The second direction is perpendicular to the first direction.
[0012] In some embodiments, the power P of the laser is in the range of 2W≤P≤1000W.
[0013] In some embodiments, the first material includes any one of nickel, titanium, copper, aluminum, iron, cobalt, zirconium, chromium, molybdenum, carbon-based materials, silicon, aluminum, magnesium, copper, zinc, silver, palladium, platinum, tin, tungsten, niobium, cobalt, gold, beryllium, vanadium, boron, nitrogen, and phosphorus; The second material includes any one of nickel, titanium, copper, aluminum, iron, cobalt, zirconium, chromium, molybdenum, carbon-based materials, silicon, aluminum, magnesium, copper, zinc, silver, palladium, platinum, tin, tungsten, niobium, cobalt, gold, beryllium, vanadium, boron, nitrogen, and phosphorus; The first material is different from the second material.
[0014] In some embodiments, the plurality of materials includes three or more elements, and the number of atoms and molecules of each element is between 0.05% and 80%.
[0015] In some embodiments, the first material is a plate, the second material is a plate, and the second material is thicker than the first material; or, The first material is a powder material, and the second material is a powder material; or, The first material is powder material, and the second material is plate material.
[0016] According to the above embodiments, the beneficial effects of the present invention are: The material modification method of the present invention comprises the following steps: S101: Melting and mixing a plurality of materials to form an alloy material; wherein the plurality of materials include a first material and a second material; S103: removing the first material in the alloy material.
[0017] The material modification method proposed in the present invention directly generates the required alloy structure on the substrate, avoiding the problems caused by secondary adhesion. In particular, the method of the present invention uses a variety of materials to melt and mix into an alloy, and can accurately control the depth and position of the alloying in three-dimensional space, achieving a highly customized microstructure design of the product, that is, the present invention can design the pore structure.
[0018] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0020] Figure 1 A flow chart of a method for material modification in one embodiment of the present invention; Figure 2 is a flow chart of a method for preparing a nickel-based electrode in one embodiment of the present invention; Figure 3 The figure is a flow chart of a method for preparing a titanium-based electrode in one embodiment of the present invention.
[0021] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.
[0024] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features limited to "first" and "second" may explicitly or implicitly include at least one of the features. In addition, if "and / or", "and / or" or "and / or" appears in the full text, its meaning includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0025] Reference below Figures 1 to 3 A method for material modification according to an embodiment of the present invention will be described.
[0026] Reference Figure 1 In some embodiments, the method of modifying the material of the present application includes: S101: Melting and mixing a plurality of materials to form an alloy material, wherein the plurality of materials include a first material and a second material.
[0027] S103: removing the first material in the alloy material.
[0028] The method of the present application selects a substrate and an auxiliary material. For example, the second material is used as the substrate and the first material is used as the auxiliary material. These materials are melted at high temperature to form an alloy body. After the alloy material is formed, the first material is selectively removed by physical or chemical methods, leaving a skeleton structure composed of the second material. At this time, the second material as the product has a number of micropores and an increased specific surface area, which is conducive to improving the reaction rate of the second material in practical applications. In addition, the method of the present invention directly generates the required alloy structure on the substrate, avoiding the problems caused by secondary adhesion.
[0029] Furthermore, multiple materials are melted and mixed to form an alloy structure. These materials can either alloy with the substrate or form an intermediate compound structure, thereby providing a basis for the customization of the final microstructure in the subsequent dealloying step. In other words, multiple materials are melted and mixed into an alloy, and the depth and position of the alloying can be precisely controlled in three-dimensional space, achieving a highly customized microstructure design for the product, that is, the present invention can design the pore structure, such as the size, shape and distribution of the voids. This not only helps to improve the performance of the material, such as enhancing mechanical strength and improving thermal conductivity, but also gives the material special physical or chemical functions, such as catalytic activity and sound absorption properties.
[0030] As to why the pore structure of the product can be designed after melting and mixing multiple materials, specifically, taking the mixing of 10 materials as an example, the 10 materials are mixed together in different proportions, then under the microstructure, there are lattices with different doping, that is, the lattices are different after doping. After doping, the lattice can be designed into a specific form to meet the needs, so that the processing of the 3D metal microstructure can be realized. In addition, the entropy value of the alloy material is changed by the laser's dwell position / dwelling time or power to achieve the purpose of structural design of the final pores.
[0031] In addition, laser can also be melted by multiple scanning layers. The base material can be aluminum foil or a mixture of different metal powders. In this way, different layers will form different lattices. Multiple layers stacked together, scanning power, laser heat (dwelling time) make the depth of laser action different. The focus of the laser can be inside the depth or on the surface; for example, the laser can be focused at a depth of 100 microns in the metal instead of on the surface. The scanning depth is determined by the wavelength of the laser. Different materials accept different wavelengths, so the infrared transmittance is relatively high.
[0032] For example, the present application can be used in electrode preparation processes and gas desorption processes. In the electrode preparation process, a larger specific surface area means more active sites available for electrochemical reactions, thereby improving the charge and discharge efficiency and energy density of the electrode; a complex microstructure helps to improve the thermal conductivity of the electrode material, allowing heat to be dissipated more evenly and preventing local overheating, which is essential for improving the safety and service life of the battery; appropriate porosity and connectivity are also conducive to alleviating the stress caused by volume changes, especially the significant expansion / contraction effect of certain electrode materials (such as silicon-based negative electrodes) during the lithium insertion / extraction process. Taking a specific implementation as an example, for example, a suitable transition metal oxide can be selected as the second material (such as lithium cobalt oxide), and graphite or another material that is easily corroded and removed can be selected as the first material. By high-temperature melt mixing and then selectively removing the first material, the product can obtain a lithium cobalt oxide framework with rich micropores and a large specific surface area. Such a structure not only increases the storage capacity of lithium ions, but also promotes the rapid insertion and extraction of lithium ions, thereby improving the energy density and power density of the battery, and can greatly improve the electrochemical performance of the electrode material without sacrificing mechanical strength.
[0033] In the gas desorption process, the product material of the present application has a larger specific surface area, which means that more gas molecules can contact the surface of the product material, thereby improving the adsorption efficiency and capacity of the gas; the complex microstructure in the product material helps to optimize the diffusion path of the gas molecules and reduce resistance; the tiny grooves and pores in the product material can serve as channels for the gas molecules to escape; the specific geometric arrangement in the product material may induce the airflow to produce a vortex effect or other flow patterns, further increasing the desorption rate, and the specific geometric arrangement can induce the airflow to produce a vortex effect or other flow patterns, further increasing the desorption rate.
[0034] It should be noted that the first material can be a single substance or an alloy, and the second material can be a single substance or an alloy. The specific composition of the first material and the second material is designed according to actual needs. The first material and the second material can be metal materials or non-metal materials, and their composition is determined according to actual needs.
[0035] Regarding the method of melting and mixing multiple materials, there may be various methods such as laser melting, high frequency induction furnace melting, medium frequency induction furnace melting, arc melting, etc. Even in some embodiments, chemical methods may be used, such as reacting a solution with the first material and the second material to form the desired alloy material from the first material and the second material.
[0036] Regarding the removal of the first material in the alloy material, it should be noted that the first material in the alloy does not necessarily need to be completely removed, for example, only 90% of the first material is removed, and it is only necessary to ensure that the product material meets the process standards.
[0037] In some embodiments, in order to further optimize the process flow of material surface modification and the performance of the final product, more parameter control methods can be introduced. For example, in a multi-step melting process, the temperature and time parameters can be adjusted in stages during the melting step to make the fusion between different materials more uniform and reduce defects. In addition, other trace elements (such as rare earth elements) can also be added to refine the grains and improve the overall performance of the alloy.
[0038] The choice of environmental conditions during the melting process is also very important. Different gas atmospheres (such as argon and nitrogen) will affect the changes in the alloy composition, and thus affect the effect of subsequent removal of the first material. In some embodiments, the type of protective gas during melting is reasonably selected and its purity is strictly controlled to ensure product quality.
[0039] In some embodiments, the plurality of materials includes only the first material and the second material. In some embodiments, the plurality of materials includes three or more materials, and the three or more materials include the first material and the second material.
[0040] Introducing a third or even more types of materials can improve the overall performance of the alloy by taking advantage of their unique properties. For example, some elements can significantly improve the corrosion resistance of the alloy, while others help to enhance its hardness or toughness. By adjusting the proportions of each component, new materials with excellent properties can be obtained. In addition, in the case of three or more materials, in addition to considering the role of a single material, it is also necessary to pay attention to the interaction between the components. The right combination can produce a synergistic effect between the components, creating new functions or higher levels of performance that cannot be achieved with a single material. For example, a specific ratio of aluminum-magnesium-titanium alloy can significantly increase strength while maintaining lightness.
[0041] In some embodiments, the first material can be a plate or a powder material, and the form of the doped material can be diversified to meet different processing requirements. When the first material is in the form of a plate, such as aluminum foil, nickel foil, etc., it is convenient to evenly cover a large area; when the first material is in the form of a powder material, such as aluminum powder, silicon powder, etc., it can be evenly attached to the surface of the parent material by spraying or other means, and is suitable for fine processing. Various forms of materials can be used alone or in combination to enhance the complexity of alloying and the ability to control the structure.
[0042] In one embodiment, removing the second material from the alloy material includes reacting with the first material through a solution or steam to remove the first material from the alloy material. Specifically, when the alloy material is placed in a solution of specific chemical properties or exposed to a specific type of steam environment, the solution or steam will selectively react chemically with the first material, causing the first material to become a liquid or gaseous state, thereby separating from the second material without significantly affecting the second material or other materials. For example, if the first material is aluminum, a sodium hydroxide solution can be used as a solvent because aluminum can react with alkaline solution to form soluble aluminates, causing aluminum to become liquid and thus separated from the product material, and only the first material will be corroded and eventually removed, while other components in the alloy remain unchanged.
[0043] In one embodiment, removing the second material from the alloy material includes reacting with the first material and at least one other material through a solution or steam, respectively, to remove two or more materials from the alloy material. The materials used to form the alloy in the present invention may be two materials or multiple materials, and the materials removed from the alloy material in the present invention may be only one material or multiple materials. By chemical reactions, the materials and proportions of the alloy are selectively formulated, and different pore structures can be designed on the final product to meet actual needs.
[0044] When two materials of different properties are melted and cooled to solidify, they will form a certain phase structure according to their respective characteristics. If there is a significant difference in solubility or thermal expansion coefficient between the two materials, one of the materials can be removed by selective etching in the subsequent processing. For example, a chemical solution is used to react with the first material without affecting the second material, so that the first material can be separated from the alloy. This process is based on the difference in chemical affinity and stability between the materials, thereby achieving directional removal.
[0045] It is understood that the dealloying process of the present invention is not limited to solution chemical dealloying (such as potassium hydroxide or sodium hydroxide solution), but can also include other physical, chemical or electrochemical methods to achieve complex microstructure customization. For example, in the form of chemical corrosion, specific elements are selectively dissolved; in the form of electrochemical dealloying, the target alloy components are dissolved by electrochemical means to accurately control the desorption depth; in the form of physical dealloying, certain volatile components in the product material are dissolved after heat treatment.
[0046] It is understood that in some embodiments, in order to further improve the removal efficiency and selectivity, a multi-step removal process can be used. First, the surface of the first material can be activated by pretreatment to make it more susceptible to reaction with the solution or steam. For example, for some metal materials, their surface activity can be increased by slight physical grinding or electrochemical polishing. Then, the pretreated alloy is placed in a solution or steam environment containing a specific catalyst to accelerate the speed of the chemical reaction.
[0047] In some embodiments, a combined removal strategy can be used, that is, a plurality of different types of solutions or steam are used simultaneously, each of which is optimized for a different type of first material. Specifically, when there are two or more first materials that need to be removed, a composite system can be designed, which includes multiple independently controlled reaction chambers, and the environmental conditions in each chamber can be adjusted according to the characteristics of the first material to be removed. This can achieve a more complex and efficient multi-material removal scheme, which is particularly suitable for processing complex alloy systems composed of multiple elements. Taking a specific embodiment as an example, when the parent material (the first material before being processed and the second material waiting to be processed) contains multiple impurities, certain components can be removed in steps by combining different dealloying methods. For example, aluminum is first dissolved with a strong base (such as potassium hydroxide), and then magnesium is dissolved with an acidic solution (such as hydrogen chloride), thereby forming a multi-level microporous structure on the same substrate; or specific metal components are selectively removed by electrochemical means to achieve a complex gradient structure. Through the above method, the surface structure of the product material after dealloying can be a microporous structure, a gradient pore structure or a nanoscale porous network.
[0048] In some embodiments, ultrasonic assistance is used to enhance the kinetics of the removal process. The cavitation effect generated by ultrasound can promote the contact area between the solution or vapor and the first material and destroy the passive film that may be formed, thereby making the removal process faster and more thorough.
[0049] In some embodiments, melt mixing a plurality of materials to form an alloy material comprises: Mixing a plurality of materials by laser melting to form an alloy material; and / or, The laser is controlled to scan multiple materials multiple times to form an alloy material.
[0050] In actual operation, by focusing a high-energy-density laser beam onto the surface of the material to be processed, the local area can be quickly heated to above the melting point, so that different types of powdered or foil-like raw materials can be fully fused together to form a uniformly distributed alloy layer. This process is not limited to a single scan, but the laser parameters (such as power, scanning speed, spot size) and the number of repeated scans can be adjusted as needed to ensure the ideal metallurgical bonding between the components, and finally obtain an alloy material with excellent performance.
[0051] In principle, laser melting technology relies on rapid heating and cooling mechanisms, which enables the material to change from solid to liquid and then to solid in a very short time. During this process, atoms of different materials diffuse and reorganize fully to form a new crystal structure. Compared with traditional casting, laser melting has higher precision and controllability. It can precisely heat small areas and avoid thermal stress problems caused by overall heating. In addition, due to the high concentration of laser energy, the temperature gradient in the molten pool is very large, which is conducive to the formation of fine-grained structure, thereby improving the mechanical strength and other physical and chemical properties of the alloy material.
[0052] In some embodiments, the laser power and scanning speed are dynamically adjusted to achieve precise control of the surface temperature and energy distribution of the parent material. Specifically, high power and low speed can concentrate the energy and promote deep alloying; low power and high speed can achieve shallow alloying of the surface layer; the combined application of power and scanning speed in different areas can form gradient alloy structures of different depths in the parent material.
[0053] It is understandable that in some embodiments, in order to further optimize the laser melting process, measures such as controlling the laser focus dwell time and adjusting the laser path planning can be taken. For example, appropriately extending the laser dwell time at a certain position can keep the molten pool long enough to promote composition homogenization; a reasonable design of the laser movement trajectory helps to ensure that the entire workpiece surface is treated uniformly. In addition, considering that different material combinations may produce different fusion behaviors, the laser parameters can also be flexibly adjusted according to actual conditions to ensure the best melting effect.
[0054] In some embodiments, laser processing can be performed to simultaneously incorporate multiple dopant materials into the base material at one time, or it can be performed in multiple times to gradually adjust the alloy depth and composition. Specifically, one-time processing can quickly form a uniform shallow or deep alloy structure; multiple processing can introduce different dopant materials each time, gradually adjust the laser focus and power, and thus form a gradient change from the surface to the deep layer in the base material.
[0055] In addition, the order of adding different impurities and their alloying sequence also have an important impact on the final structure. In some embodiments, low-melting-point materials are first incorporated to form a shallow surface structure, and then high-melting-point materials are incorporated to form a deep support structure; in some embodiments, multiple laser processing is repeated to control the alloying states of the surface and deep layers to interact with each other, further enriching the final structure.
[0056] In some embodiments, melt mixing a plurality of materials to form an alloy material comprises: The laser focus is controlled to stay in at least one region of multiple materials for a time t, where the range of t is: 1ns≤t≤40s, for example, t can be 1ns, 10s, 20s, 30s, or 40s.
[0057] The laser focus dwell time directly affects the existence time and cooling rate of the molten pool. Properly extending the dwell time can keep the molten pool long enough to promote atomic diffusion and recombination between the components, which is conducive to the formation of a denser and more uniform alloy structure. For example, when dealing with more complex geometries or workpieces that require special attention to the uniformity of composition, a longer dwell time (such as close to 40s) can be set to promote more thorough metallurgical bonding; for simple planes or applications with high requirements for fusion speed, a shorter time (such as about 1ns) can be selected. By reasonably controlling the laser's dwell time, it is possible to ensure that different materials are fully fused and form a uniformly distributed alloy layer.
[0058] In addition, by adjusting the residence time, the temperature gradient in the molten pool can be controlled, thereby affecting the size and morphology of the final crystals. This not only helps to improve the mechanical properties of the alloy material, but also improves its surface characteristics, such as increasing hardness and enhancing corrosion resistance.
[0059] It is understandable that the dwell time of the laser focus can be further refined and adjusted according to the specific conditions of the actual processing object. For example, when processing thicker workpieces, it may be necessary to increase the dwell time appropriately to ensure that the internal material can also obtain enough heat for fusion; when processing thin-walled structures, the dwell time should be shortened as much as possible to prevent deformation caused by overheating. In addition, for some special alloy systems, other process parameters (such as laser power and scanning speed) can also be combined for optimization to find the optimal dwell time window.
[0060] In some embodiments, melt mixing a plurality of materials to form an alloy material comprises: Controlling the laser so that the focus of the laser passes through at least the first area and the second area; and / or, Controlling the laser so that the focus of the laser passes through at least the third area and the fourth area; Wherein, along the first direction, the first area and the second area are distributed at intervals, along the second direction, the third area and the fourth area are distributed at intervals, and the second direction is perpendicular to the first direction.
[0061] The present invention uses laser to focus on different depth areas of the parent material, and controls the depth range of the alloying reaction by adjusting the laser focal length and power. The specific implementation includes: adjusting the laser focus position to cover the shallow surface or deep layer of the parent material; local heating in different depth areas so that the parent material and the doped material form different alloy states. This multi-area scanning strategy is adopted to overcome the limitations of traditional unidirectional scanning. Traditional unidirectional scanning often finds it difficult to take into account the differences in material properties in different directions, which may lead to problems such as poor local fusion or uneven composition. By introducing spaced distribution areas in multiple directions, the anisotropic characteristics of the material can be better adapted to ensure the fusion quality in each direction. In addition, scanning along different directions can also help to disperse heat and reduce defects caused by local overheating, such as cracks, pores, etc. The main beneficial effect of this method is that it can significantly improve the overall performance of the alloy material, including but not limited to strength, toughness, wear resistance and fatigue resistance. For example, when manufacturing alloy components with complex three-dimensional structures, all key parts can be covered through the designed laser movement trajectory to avoid missing any details, thereby obtaining an ideal alloying effect.
[0062] It can be understood that in some embodiments, the first direction is the depth direction of the alloy material, and the second direction can be understood as a direction parallel to the surface of the alloy material. The first region and the second region are spaced apart in the first direction, and the laser can be focused on the first region and the second region, that is, the laser can alloy the different regions of the parent material in the depth direction; the third region and the fourth region are spaced apart in the second direction, and the laser can be focused on the third region and the fourth region. In summary, the laser can alloy any position of the parent material. In other words, the first region and the second region are different positions in the z-axis direction, and the third region and the fourth region are different positions in the xy plane relative to the horizontal plane of the z-axis, so the laser of the present application can be focused on any position in the xyz coordinate system, that is, the present application can realize three-dimensional laser engraving. With such a design, the present application can pattern the product material, and when used for electrode production, it can realize precise customization of the microstructure of the electrode surface.
[0063] In some embodiments, the laser can be focused at a certain depth inside the base material to process the material, or the laser can be focused on the surface of the base material so that the surface of the base material is subjected to the high temperature of the laser, and then the heat is transferred to a certain depth of the base material by heat conduction.
[0064] In some embodiments, the power P of the laser satisfies 2W≤P≤1000W, for example, P is 2W, 40W, 60W, 500W, 1000W. The selection of this power range is based on a comprehensive consideration of material properties and the desired melting effect. When the laser power is set to 2W, sufficient energy input can be ensured to start the melting process, but the material will not be overheated to cause overburning or deformation; when the power is increased to 1000W, the melting efficiency and speed can be maximized while ensuring safety.
[0065] In some embodiments, considering the different characteristics of laser absorption rates of different materials, a multi-wavelength or multi-mode laser system can be introduced for composite melting. In this case, each wavelength of laser can be optimized for a specific material to achieve the best melting effect. For example, for metal materials with high reflectivity, infrared lasers can be selected; for ceramic materials with high transparency, ultraviolet lasers can be selected. Such a design not only improves energy utilization, but also broadens the application scope of laser melting technology.
[0066] In some embodiments, the second material is thicker than the first material. The second material is used as a substrate and is designed to have a larger thickness to ensure the mechanical rigidity of the product material.
[0067] Next, the material modification method of the present invention is described with a specific process. Specifically, in some embodiments, during the surface modification of the material, aluminum is first mixed with nickel or titanium by laser melting technology to form a molten layer 100 microns thick. In this step, the laser focus will sweep across the surface of the material, so that the first 100 microns of aluminum are completely melted and enter a molten state together with the second material (such as nickel or titanium), forming a magma-like alloy layer. Once this layer of melt cools down, a new alloy structure is formed. On this basis, additional layers or layers of materials can be added as needed. These additional layers can be composed of different metals, and the order and combination of their addition will affect the final alloy morphology.
[0068] In order to ensure the uniformity of the internal structure of the alloy, further processing can be performed through a secondary scan. At this stage, the laser focus can stay in the inner layer for a longer time (for example, 20 seconds to 30 seconds) to promote the internal alloying process, while the outer part may only be affected by heat without being directly focused. This treatment method not only relies on direct laser heating, but also utilizes the principle of heat conduction, that is, heat gradually penetrates from the surface to the interior of the material, so that different areas can achieve different degrees of alloying.
[0069] In addition, laser power and focus dwell time are key parameters for controlling the degree of alloying, and patent protection should cover the precise control of these parameters, including but not limited to the laser power range (such as 2W to 1000W), focus dwell time (such as 1ns to 40s), and laser path planning (such as the first and second regions spaced apart along the first direction, and the third and fourth regions spaced apart along the second direction perpendicular to the first direction). This method is suitable for the first material in the form of a sheet or powder, and allows the second material to have a greater thickness to meet different application requirements.
[0070] In some embodiments, taking the application of the present application in electrode production as an example, the material modification method of the present application includes the following steps: First, the substrate is prepared, nickel, titanium or other metals are selected as the substrate material, and a thin layer of aluminum is covered on its surface, which can be in the form of a film or powder. The next step is the laser engraving step, which uses a high-power laser to engrave the aluminum layer, and achieves patterning or non-patterning processing according to requirements; laser engraving can be performed once or multiple times, and different temperature gradients and aluminum concentration distributions can be formed by precisely adjusting parameters such as laser power, scanning speed and residence time to meet specific application requirements.
[0071] During the laser engraving process, the local high temperature caused by the laser causes element diffusion and high-temperature alloying between the aluminum layer and the base metal, forming an intermetallic compound layer or alloy layer with a specific gradient on the surface of the base. Then, the dealloying stage is entered, and the laser-processed base is placed in a selected dealloying solution (such as potassium hydroxide solution) to selectively dissolve the aluminum component. By controlling the solution concentration and the dealloying time, the base surface structure and its specific surface area are further regulated, thereby optimizing the microscopic morphology of the final product.
[0072] Finally, the electrode surface formed after the above treatment exhibits the characteristics of high specific surface area and microscopic porous structure. This special surface structure can be optimized and adjusted according to the needs of specific applications to ensure that the material has excellent physical and chemical properties and is suitable for a variety of high-end application scenarios such as high-efficiency catalyst carriers and high-performance battery electrodes.
[0073] Further, refer to Figure 2 , taking the preparation of nickel-based electrodes as an example, the steps include: S201: A nickel sheet with a thickness of 0.5 mm is used as the substrate, and a 10 µm aluminum film is evenly coated on the surface; S202: patterning the aluminum layer using a laser device with a laser power of 30 W, a scanning speed of 200 mm / s, and a dwell time of 1 ms; S203: forming a gradient distribution of nickel-aluminum alloy in the engraving area; S204: placing the processed substrate in a 1M KOH solution for 30 minutes to dissolve aluminum components on the surface; S205: A Raney nickel electrode with a microporous structure was obtained, and its catalytic activity in the hydrogen evolution reaction was tested. It was found that its specific surface area was significantly improved and its catalytic performance was excellent.
[0074] Reference Figure 3 , taking the preparation of titanium-based electrodes as an example, the following steps are included: S301: Pure titanium sheet is used as the substrate, and aluminum powder is evenly sprayed on the surface, with an aluminum layer thickness of 20µm; S302: non-patterned engraving of the aluminum layer is performed using a laser device with a laser power of 50 W, a scanning speed of 150 mm / s, and a dwell time of 2 ms; S303: forming a multi-layer titanium-aluminum alloy structure on the titanium surface; S304: placing the processed substrate in a 2M NaOH solution for 60 minutes to obtain a high-efficiency electrode with a porous titanium surface; S305: The electrode exhibits excellent stability and catalytic performance in electrochemical oxidation reactions.
[0075] In addition, regarding the first material and the second material of the present invention, it should be noted that the multiple materials include three or more elements, and the number of atoms and molecules of each element is between 0.05% and 80%. In some embodiments, the first material is a plate, and the second material is a plate, and the thickness of the second material is greater than that of the first material. In some embodiments, the first material is a powder material, and the second material is a powder material. In some embodiments, the first material is a powder material, and the second material is a plate, for example, the plate includes any form, such as strips, thinner whole plates, structures of different shapes and thicknesses, and common forms such as aluminum foil.
[0076] In some embodiments, the first material includes any one of nickel, titanium, copper, aluminum, iron, cobalt, zirconium, chromium, molybdenum, carbon-based materials, silicon, aluminum, magnesium, copper, zinc, silver, palladium, platinum, tin, tungsten, niobium, cobalt, gold, beryllium, vanadium, boron, nitrogen, and phosphorus. The second material includes any one of nickel, titanium, copper, aluminum, iron, cobalt, zirconium, chromium, molybdenum, carbon-based materials, silicon, aluminum, magnesium, copper, zinc, silver, palladium, platinum, tin, tungsten, niobium, cobalt, gold, beryllium, vanadium, boron, nitrogen, and phosphorus. The first material is different from the second material.
[0077] Specifically, the following is a list of substrate materials and attachment materials with potential commercial value in industrial applications for this application. Based on different application requirements, the material combination can be used to form a variety of functionalized alloys (such as high specific surface area electrodes, corrosion-resistant coatings, catalysts, etc.). These materials have both processability, performance control potential and market availability.
[0078] 1. List of base materials The following materials can be used as base materials for alloying process, and the selection criteria include high conductivity, mechanical strength, corrosion resistance and economy: (1) Metal base material Nickel (Ni): used in high-efficiency electrodes, catalysts and corrosion-resistant alloys.
[0079] Titanium (Ti): It has good corrosion resistance and light weight, and is suitable for aviation, chemical and biomedical fields.
[0080] Copper (Cu): Highly conductive, suitable for the electrical industry.
[0081] Aluminum (Al): Lightweight and suitable for lightweight design.
[0082] Iron (Fe): Widely used in industry to form a variety of iron-based alloys (such as stainless steel).
[0083] Cobalt (Co): used in the fields of magnetic materials and catalysts.
[0084] Zirconium (Zr): High corrosion resistance, suitable for chemical and nuclear industry applications.
[0085] Chromium (Cr): It can enhance corrosion resistance and is used in stainless steel and surface strengthening.
[0086] Molybdenum (Mo): Improves the strength and high temperature resistance of materials and is widely used in high temperature environments.
[0087] (2) Non-metallic substrate materials (need to be surface metallized by plating or other methods) Carbon-based materials (such as graphite, carbon fiber): suitable for lightweight, high conductivity applications.
[0088] Silicon (Si): Mainly used in semiconductor and energy fields.
[0089] 2. List of attached materials The following materials can be used to cover or dope substrate surfaces to form alloys or surface composites: (1) Metal attachment materials Aluminum (Al): Lightweight and easy to form porous structures, used in catalysts and corrosion-resistant alloys.
[0090] Magnesium (Mg): It forms lightweight alloys with base materials and is widely used in the automotive and aviation fields.
[0091] Copper (Cu): Improves electrical conductivity and antibacterial properties.
[0092] Zinc (Zn): Used in anti-corrosion coatings (such as galvanizing).
[0093] Silver (Ag): Improves electrical conductivity and antibacterial properties.
[0094] Palladium (Pd): used in catalysis and hydrogen storage applications.
[0095] Platinum (Pt): highly efficient catalyst material.
[0096] Tin (Sn): Used in oxidation protection coatings and solder alloys.
[0097] Tungsten (W): Improves wear resistance and high temperature performance.
[0098] Niobium (Nb): Increases oxidation resistance and mechanical strength.
[0099] Cobalt (Co): Improves magnetic properties and corrosion resistance.
[0100] Gold (Au): Provides high electrical conductivity and chemical inertness.
[0101] Beryllium (Be): High strength, lightweight, used in aviation.
[0102] Vanadium (V): Enhances fatigue and wear resistance.
[0103] (2) Non-metallic attachment materials Silicon (Si): can form silicide alloys to improve thermal stability.
[0104] Carbon (C): forms carbides, significantly improving hardness and wear resistance.
[0105] Boron (B): forms borides, increasing high temperature resistance and corrosion resistance.
[0106] Nitrogen (N): forms nitrides and is suitable for superhard coatings.
[0107] Phosphorus (P): Used in certain corrosion-resistant coatings and lubricating coatings.
[0108] 3. Alloy combination examples The following are typical combinations of base materials and adhesive materials and their application areas: (1) Nickel-based alloy Ni-Al (Nickel Aluminum Alloy): Used for high surface area catalysts (such as Raney Nickel).
[0109] Ni-Ti (nickel-titanium alloy): used in shape memory materials and medical devices.
[0110] Ni-Cr (nickel-chromium alloy): used for high temperature corrosion resistant coatings.
[0111] Ni-Cu (nickel-copper alloy): used for structural parts resistant to seawater corrosion.
[0112] (2) Titanium-based alloys Ti-Al (titanium aluminum alloy): lightweight, high-strength material used in aviation and biomedical applications.
[0113] Ti-Si (titanium silicon alloy): improves surface wear resistance and oxidation resistance.
[0114] Ti-B (titanium-boron alloy): Enhanced high temperature mechanical properties.
[0115] (3) Iron-based alloys Fe-Cr (Iron-Chromium alloy): widely used in stainless steel and corrosion resistance fields.
[0116] Fe-Al (iron-aluminum alloy): lightweight and high temperature resistant material.
[0117] Fe-C (Iron-Carbon Alloy): Enhanced strength and hardness, suitable for tool making.
[0118] (4) Aluminum-based alloys Al-Mg (aluminum-magnesium alloy): Improves corrosion resistance and is used in marine equipment.
[0119] Al-Cu (aluminum-copper alloy): used in the aviation industry.
[0120] Al-Si (aluminum silicon alloy): used for engine components and automobile lightweight design.
[0121] (5) Copper-based alloy Cu-Zn (Copper-Zinc Alloy / Brass): Used for decorative and corrosion-resistant equipment.
[0122] Cu-Ni (Copper-Nickel Alloy): Improves corrosion resistance and is suitable for the shipbuilding industry.
[0123] (6) Cobalt-based alloy Co-Cr (Cobalt-Chromium alloy): used in dental and orthopedic implants.
[0124] Co-W (Cobalt Tungsten): Suitable for cutting tools and wear-resistant parts.
[0125] (7) Zirconium-based alloys Zr-Ti (Zirconium-Titanium Alloy): High corrosion resistance and biocompatibility, used in nuclear industry and biomedicine.
[0126] (8) Other combinations Mg-Si (magnesium silicon alloy): used for lightweight structural materials.
[0127] Sn-B (Tin-Boron alloy): used in certain electronic devices.
[0128] Cr-N (chromium nitrogen alloy): forms an ultra-hard, wear-resistant coating.
[0129] 4. Commercial value and application prospects The above material combination can produce practical applications in multiple industrial fields, including: (1) New energy field: high-efficiency catalyst electrodes (such as water electrolysis and fuel cells).
[0130] (2) Aerospace: lightweight high-strength alloys and high-temperature resistant coatings.
[0131] (3) Chemical equipment: corrosion-resistant alloys and protective coatings.
[0132] (4) Medical devices: biocompatible alloys and high surface area bone implants.
[0133] (5) Electronics industry: high conductivity and wear-resistant materials.
[0134] Through the flexible combination of base materials and attachment materials, it can meet the requirements of different fields for mechanical properties, conductivity, corrosion resistance and other performances, and has significant commercial application value and market potential. In some embodiments, the various materials of the present invention include multi-element alloys. Multi-element alloys (High-EntropyAlloys, HEAs or Complex Concentrated Alloys, CCAs) are material systems composed of multiple elements (usually 5 or more main elements, each element atomic fraction between 5%-35%), with excellent mechanical properties, corrosion resistance, high temperature resistance and other special functions. These materials have gradually become a research hotspot in the field of materials science due to their unique structure and properties, especially in the fields of high-performance electrodes, aerospace, energy and catalysis, and have extensive commercial value.
[0135] The following is a detailed material classification and potential combination solutions for multi-element alloys, covering a wide range of substrates and attached materials.
[0136] 1. Characteristics of multi-element alloys 1. High entropy effect The entropy effect in multi-element systems causes alloys to tend toward simple crystal structures (such as FCC, BCC, and HCP), thereby improving the stability of the material.
[0137] 2. Solid solution strengthening The solid solution formed by multiple elements significantly enhances the strength and hardness of the alloy.
[0138] 3. Corrosion resistance and high temperature stability Multi-element alloys exhibit excellent performance in harsh environments (such as high temperature and severe corrosion conditions).
[0139] 4. Customizability Depending on the combination of different elements, the physical, chemical and mechanical properties of the material can be tailored.
[0140] 2. Classification of multi-element alloys 1. Alloys with face-centered cubic structure (FCC) as the main structure (1) Main characteristics: good ductility, strong corrosion resistance, suitable for low temperature applications.
[0141] (2) Typical element combinations: Ni-Co-Cr-Fe-Mn; Ni-Co-Cr-Al-Mn; Cu-Ni-Co-Cr-Mn; Co-Cr-Fe-Ni-Cu; 2. Alloys with body-centered cubic structure (BCC) as the main structure (1) Main characteristics: high hardness, high melting point, suitable for high temperature and high strength applications.
[0142] (2) Typical element combinations: Ti-Zr-Hf-Nb-Ta; Al-Ti-Zr-Nb-Mo; Cr-Mo-Ti-WV; Nb-Ti-Al-V-Zr; 3. Alloys with mixed structure (FCC+BCC) (1) Main characteristics: It has both ductility and strength, and its performance can be controlled by adjusting the ratio of elements.
[0143] (2) Typical element combinations: Al-Co-Cr-Fe-Ni; Al-Mo-Cr-Nb-Ti; Fe-Co-Ni-Cr-Al; Ti-V-Cr-Al-Mn; 4. Intermetallic compound type multi-element alloy (1) Main features: stable structure, good high temperature resistance, used for coatings and catalysts.
[0144] (2) Typical element combinations: Ti-Al-Nb-Mo-Si; Cr-Ni-Co-Al-Ti; Fe-Ni-Cr-Al-Mn; 5. Amorphous multi-element alloys (1) Main characteristics: no crystal structure, high hardness, strong wear resistance, and excellent catalytic and electrochemical properties.
[0145] (2) Typical element combinations: Fe-Cr-Mn-Co-Ni; Zr-Ti-Ni-Cu-Al; Pd-Cu-Ni-P-Si; 3. List of common multi-element alloy materials (1) Base material (parent material) Metal substrate used to support the multi-element alloy layer: Nickel (Ni) Titanium (Ti) Aluminum (Al) Copper (Cu) Iron (Fe) Cobalt (Co) Chromium (Cr) Molybdenum (Mo) Tantalum (Ta) Zirconium (Zr) (2) Adhesive materials (alloy layer elements) It can be used as a key component in multi-element alloys and is classified by main functions: Elements that enhance mechanical properties Titanium (Ti), aluminum (Al), vanadium (V), zirconium (Zr), niobium (Nb); Elements that improve corrosion resistance Nickel (Ni), chromium (Cr), molybdenum (Mo), cobalt (Co), manganese (Mn); Elements that enhance high temperature performance Tungsten (W), Tantalum (Ta), Hafnium (Hf), Niobium (Nb); Elements that improve conductivity or catalytic properties Copper (Cu), silver (Ag), gold (Au), palladium (Pd), platinum (Pt); Optimized hardness and wear resistance Boron (B), Carbon (C), Silicon (Si), Nitrogen (N).
[0146] 4. Multi-element alloy combinations in application scenarios 1. High-efficiency electrode materials Ni-Co-Cr-Fe-Mn: Suitable for water electrolysis and fuel cell electrodes, with high catalytic activity and corrosion resistance.
[0147] Ti-Zr-Hf-Nb-Ta: Resistant to high temperature and high pressure, suitable for special electrolysis environment.
[0148] 2. Corrosion-resistant coating Al-Co-Cr-Fe-Ni: widely used in petrochemical industry and marine engineering, with strong corrosion and wear resistance.
[0149] Cr-Mo-Ti-WV: Suitable for harsh chemical environments, with excellent corrosion resistance and high temperature stability.
[0150] 3. Aerospace structural materials Ti-Al-Nb-Mo-Si: light and high-strength, resistant to high temperature oxidation, widely used in aircraft engines.
[0151] Ni-Co-Cr-Al-Ti: High temperature resistant coating used for turbine blades and thermal barrier coatings.
[0152] 4. Medical implants Co-Cr-Mo-Ti: Good biocompatibility, suitable for bone implants and dental restoration materials.
[0153] Ti-Zr-Al-V: Lightweight, non-toxic, widely used in medical equipment.
[0154] 5. High temperature structural materials Cr-Mo-Ti-WV: used for high temperature furnace linings and reactors.
[0155] Nb-Ti-Al-V-Zr: has excellent mechanical properties and stability at high temperatures.
[0156] 5. Commercialization Potential (1) New energy field: Multi-element alloy electrodes can provide high efficiency and high stability in technologies such as hydrogen energy and water electrolysis.
[0157] (2) Aerospace: Lightweight, high-strength, high-temperature resistant multi-element alloys are in great demand in aerospace engines and high-temperature resistant components.
[0158] (3) Chemical industry and marine engineering: Corrosion-resistant alloy coatings are widely used in petrochemical industry and offshore equipment.
[0159] (4) Medical devices: Biocompatible alloys meet the long life and functional requirements of implants.
[0160] In summary, the material modification method proposed in the present invention directly generates the required alloy structure on the substrate, avoiding the problems caused by secondary adhesion. In addition, by focusing the laser beam at a specific depth, selective alloying inside the material can be achieved, rather than just surface treatment. This flexibility allows the construction of more complex and multifunctional metal composites. In particular, the method of the present invention uses a variety of materials to melt and mix into an alloy, and can accurately control the depth and position of the alloying in three-dimensional space, achieving a highly customized microstructure design of the product, that is, the present invention can design a pore structure to meet the needs of all walks of life.
[0161] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for material modification, characterized in that: include: Melting and mixing a plurality of materials to form an alloy material; wherein the plurality of materials include a first material and a second material; The first material in the alloy material is removed.
2. The material modification method according to claim 1, characterized in that: The plurality of materials include only the first material and the second material; or, the plurality of materials include three or more materials.
3. The material modification method according to claim 1, characterized in that: The removing the second material from the alloy material comprises: Reacting with the first material by a solution or steam to remove the first material from the alloy material; or, The solution or steam reacts with the first material and at least one other material respectively, so as to remove two or more materials in the alloy material.
4. The method according to claim 1, characterized in that: The melting and mixing of the plurality of materials to form an alloy material comprises: Mixing the plurality of materials by laser melting to form the alloy material; and / or, The laser is controlled to scan the plurality of materials multiple times to form the alloy material.
5. The material modification method according to claim 4, characterized in that: The melting and mixing of the plurality of materials to form an alloy material comprises: The laser focus is controlled to stay in at least one area of the plurality of materials for a time t, wherein the range of t is: 1ns≤t≤40s.
6. The material modification method according to claim 4, characterized in that: The melting and mixing of the plurality of materials to form an alloy material comprises: Controlling the laser so that the focus of the laser passes through at least the first area and the second area; and / or, Controlling the laser so that the focus of the laser passes through at least the third area and the fourth area; The first direction is the direction from the first material to the second material, the first region and the second region are spaced apart along the first direction, the third region and the fourth region are spaced apart along the second direction, and the second direction is perpendicular to the first direction.
7. The material modification method according to claim 6, characterized in that: The range of the laser power P is: 2W≤P≤1000W.
8. The material modification method according to claim 1, characterized in that: The first material includes any one of nickel, titanium, copper, aluminum, iron, cobalt, zirconium, chromium, molybdenum, carbon-based materials, silicon, aluminum, magnesium, copper, zinc, silver, palladium, platinum, tin, tungsten, niobium, cobalt, gold, beryllium, vanadium, boron, nitrogen, and phosphorus; The second material includes any one of nickel, titanium, copper, aluminum, iron, cobalt, zirconium, chromium, molybdenum, carbon-based materials, silicon, aluminum, magnesium, copper, zinc, silver, palladium, platinum, tin, tungsten, niobium, cobalt, gold, beryllium, vanadium, boron, nitrogen, and phosphorus; The first material is different from the second material.
9. The material modification method according to claim 1, characterized in that: The multiple materials include three or more elements, and the number of atoms and molecules of each element is between 0.05% and 80%.
10. The material modification method according to claim 1, characterized in that: The first material is a plate, the second material is a plate, and the thickness of the second material is greater than that of the first material; or, The first material is a powder material, and the second material is a powder material; or, The first material is a powder material, and the second material is a plate material.
Citation Information
Cited By
Material modification method
WO2026119283A1